Analisis Rantai Pemasaran Sayur Hidroponik: Studi Kasus di Kota Kendari - Nurhalipa; Fidina, Tsabita; Sugiarti, Shella; Tania, Putri; Zelina; Anggraini, Revi; Sarlian; Pratama, Aldi; Riska; Ma'mun, Sitti Rahma (Fakultas Pertanian Universitas Muhammadiyah kendari, 2023)
Demand for hydroponic vegetables are increasing, especially urban areas, including Kendari. This is because vegetables grown hydroponically have advantages: they are environmentally friendly, the production produced is hygienic, plant growth is faster, the quality of crop yields can be maintained and the quantity can be increased. This study aims to analyse the hydroponic vegetable marketing channel in Kendari City. The selection of respondents purposely selected on five hydroponic businesses and three traders and retailers. The results show that, there are two marketing channels, namely: Channel I from farmers - consumers; and Channel II from Farmers – collectors – market traders – consumers. Of the two channels, it is known that farmers receive the greatest profit when selling directly to consumers (Channel I), while in Channel II the highest margin is obtained by retailers of IDR 37,000/kg.